1203 How common is truly benign ms?. (1st December 2017) - Tallantyre, Emma C; Major, Paula C; Atherton, Michael J; Adam Davies, W; Pickersgill, Trevor P; Harding, Katharine E; Winter, Mia; Robertson, Neil P
Abstract : The existence of benign MS remains controversial and uncertainty remains about the frequency and pathological explanation for a favourable outcome. Defining and understanding this patient group has considerable implications for MS management. Most definitions of benign MS are centred on walking ability after 10–15 y despite the far wider impact of MS on ability. We screened a prevalent population of over 2000 patients with MS and found 275 who had unlimited walking ability despite 15 y or more of MS. We undertook detailed assessments in the most benign individuals within this group (those with longest disease durations). Assessment incorporated scores of cognition, fatigue, mood, vision, bladder symptoms and arm and leg function. All patients were defined as having relapsing-remitting MS but they showed a wide range of relapse frequency and severity. While 93% of these patients met contemporary definitions for benign MS, less than 25% were truly benign (defined as normal function in each of the domains). Patient-reported scores of MS impact correlated highly with detailed clinical assessment. Our study highlights the low prevalence of truly benign MS (estimated here as <4%) and provides early insights into its phenotypic nature, which could inform on the biological mechanisms of a favourable outcome.